Assessing the Environmental and Health Impacts of Thermal Waste and Landfill-Based Waste Management - Angga Dheta Shirajjudin Aji; Sapta Suhardono; I Wayan Koko Suryawan; Wisnu Prayogo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
According to Presidential Regulation No. 35 of 2018, which focuses on accelerating the development of waste-to-energy projects, Denpasar City in Bali has been identified as one of the key Indonesian cities for implementing these projects. The daily waste generation in Denpasar City is estimated at 750 tons. The city's sanitation strategy outlines that 20% of this waste will be reduced at its source, while the remaining 80% is managed at the final treatment site. This study employs the Life Cycle Analysis (LCA) approach to evaluate the environmental impacts of traditional landfilling and various thermal waste treatment methods. The findings reveal that gasification (Scenario 2) has the lowest Global Warming Potential (GWP), with 779,759 kg CO2 equivalent emitted, indicating its superiority in reducing greenhouse gases. In contrast, landfilling (Scenario 1) is the least favorable, with a GWP of 2,885,770 kg CO2 equivalent and a significant cancer risk due to hexavalent chromium emissions estimated at 1,634,050 kg equivalent. These results underscore the health and environmental hazards of landfilling. Further, the study delves into each treatment scenario's impact on acidification, eutrophication, global warming potential, and photochemical oxidation.